2007
DOI: 10.1093/ndt/gfl642
|View full text |Cite
|
Sign up to set email alerts
|

Reverse white-coat effect as an independent risk for microalbuminuria in treated hypertensive patients

Abstract: These findings suggest that the presence of reverse white-coat effect may be an independent risk for early renal damage in treated hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Two studies suggested that ME is an independent risk factor for target organ damage in treated hypertensive patients [2,3]. Tomiyama et al [2] showed that systolic ME is an independent risk factor for left ventricular concentric hypertrophy exclusively in treated hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies suggested that ME is an independent risk factor for target organ damage in treated hypertensive patients [2,3]. Tomiyama et al [2] showed that systolic ME is an independent risk factor for left ventricular concentric hypertrophy exclusively in treated hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…Tomiyama et al [2] showed that systolic ME is an independent risk factor for left ventricular concentric hypertrophy exclusively in treated hypertensive patients. In addition, Kato et al [3] reported that the presence of this phenomenon in treated hypertensive patients may also be an independent risk factor for early renal damage. However, both studies were carried out in treated hypertensive patients and did not provide any information on the association of ME with target organ…”
Section: Introductionmentioning
confidence: 99%
“…They found that treated elderly hypertensive patients in the home effect group most often had a history of cardiovascular disease (14). Recently, it has been reported that the reverse white-coat effect, based on office BP and daytime ambulatory BP readings, is a significant predictor for microalbuminuria and an independent risk factor for left ventricular hypertrophy in patients with treated essential hypertension (19,20). Moreover, in the Ohasama study, the white-coat effect based on the office BP and the home BP readings was not significantly related to cardiovascular mortality, while the reverse whitecoat effect was a strong predictive factor of cardiovascular risk (21).…”
Section: Characteristics Of Home Effect Patients and The Factors Thatmentioning
confidence: 99%
“…Indeed the prevalence of MH in the general population could be as high as 10%, while data obtained in several cross-sectional studies have demonstrated large differences with prevalence rates from a low of 8% to a high of 49% [3][4][5][6].A body of evidence indicates that MH is a significant predictor of cardiovascular disease, while data obtained in several cross-sectional studies have demonstrated that MH is associated with increased left ventricular mass index [7][8][9] and carotid intima-media thickness [10]. Furthermore, in longitudinal studies, MH was a strong predictor of cardiovascular outcome [11], mortality [12] and target organ damage [13,14].…”
Section: Introductionmentioning
confidence: 99%